2022
DOI: 10.22456/1982-8918.122688
|View full text |Cite
|
Sign up to set email alerts
|

Teaching online Physical Education during social distancing using Google Sites

Abstract: Covid-19 has resulted in the implementation of social distancing measures and school closures worldwide. This study explores some of the impacts, such as pedagogies, teaching strategies, reflections, and barriers of the teacher as he suddenly moved to an online teaching environment and taught PE lessons with the use of technology (Google Sites). A self-study methodology with thematic analysis was used to investigate the lead author’s experiences. Findings and discussions highlight how the teacher had to find n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In terms of content analysis, the reviewed studies considered students [39,40] as participants in physical education and sport, as well as teachers in training [41,42] and active teachers [43,44]. Regarding the technologies used in both online [48,49] and blended [47,51] teaching, different platforms and webinars [46] stood out, as well as the use of augmented reality [46] or explanatory videos in flipped classroom methodologies [46] and gamification [47], mobile applications, or e-sports competitions [48]. When analysing the results, different effects were observed depending on the level of ICT competence of students and teachers [45,52], and the negative emotional impact of the situation was confirmed for both students [53,54] and teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of content analysis, the reviewed studies considered students [39,40] as participants in physical education and sport, as well as teachers in training [41,42] and active teachers [43,44]. Regarding the technologies used in both online [48,49] and blended [47,51] teaching, different platforms and webinars [46] stood out, as well as the use of augmented reality [46] or explanatory videos in flipped classroom methodologies [46] and gamification [47], mobile applications, or e-sports competitions [48]. When analysing the results, different effects were observed depending on the level of ICT competence of students and teachers [45,52], and the negative emotional impact of the situation was confirmed for both students [53,54] and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, studies were found where the teaching modality was online, as were others that used mixed modalities. For example, Mariano et al [48,49] analysed an online teaching modality during the pandemic in which e-sports (sports video game competitions) such as Mobile Legends or Team Sports were used and the losers were penalised with additional physical exercise. Also in the online teaching modality, Kulkarni et al [50] combined the use of different technologies in a model of enhanced online engineering education.…”
Section: Digital Technologiesmentioning
confidence: 99%
“…A teacher must possess pedagogical competence alongside professional competency and specific topic instructional competency (trying to transfer the individual's content to his children in a manner they can comprehend as specified in curriculum and educational targets). Someone can establish a positive learning environment for his children's by being pedagogically competent [26][27][28][29][30][31][32]. They keep tabs on their children's' progress in terms of their cognition and memory and then adjust their actions accordingly.…”
Section: Pedagogical Approach In Sports Educationmentioning
confidence: 99%